2012
DOI: 10.1093/annhyg/mer121
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Respiratory Outbreaks Associated with Exposure to Water-Based Metalworking Fluids

Abstract: Despite a number of detailed workplace and immunological studies of asthma and alveolitis outbreaks in MWF-exposed workforces, our understanding of their aetiology remains limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…This method enables the detection of live mycobacteria and reduces the threshold of detection of these microorganisms by three orders of magnitude compared to the culturing methods [28]. Molecular methods, such as real-time PCR, and a simple, recently developed species-specific colorimetric-PCR assay have been used to detect and identify two species of NTM: M. immunogenum and Mycobacterium chelonae in the samples of MFWs [29].…”
Section: Mycobacterium Immunogenum and Other Fast Growing Mycobacteriamentioning
confidence: 99%
“…This method enables the detection of live mycobacteria and reduces the threshold of detection of these microorganisms by three orders of magnitude compared to the culturing methods [28]. Molecular methods, such as real-time PCR, and a simple, recently developed species-specific colorimetric-PCR assay have been used to detect and identify two species of NTM: M. immunogenum and Mycobacterium chelonae in the samples of MFWs [29].…”
Section: Mycobacterium Immunogenum and Other Fast Growing Mycobacteriamentioning
confidence: 99%
“…The widespread use of compressed air by machine operators, who often had much exposed skin on their arms and legs, presented a plausible route of skin exposure despite consistent use of gloves. Inhalation of MWF aerosols may irritate the throat, nose, and lung and has been associated with chronic bronchitis, asthma, hypersensitivity pneumonitis, and worsening of pre-existing respiratory problems [Burton et al 2012]. Machine operators' symptoms were consistent with MWF exposure.…”
Section: Discussionmentioning
confidence: 97%
“…MWFs are complex mixtures used to cool, lubricate, and remove metal chips from tools and parts during machining of metal stock. MWFs often contain other substances including biocides, corrosion inhibitors, metal fines, tramp oils, and biological contaminants [Burton et al 2012;NIOSH 1998a]. Inhalation of MWF aerosols may irritate the throat, nose, and lungs and has been associated with chronic bronchitis, asthma, hypersensitivity pneumonitis, and worsening of pre-existing respiratory problems [Burton et al 2012].…”
Section: Metalworking Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…MWFs often contain other substances, including biocides, corrosion inhibitors, metal fines, tramp oils, and biological contaminants. [15,16] On the basis of the analytical findings and odor characteristics, it is likely that 3,5-MDMP being produced in MWFs was causing the unpleasant, persistent odor in the facility. No research studies have reported on the toxicity of 3,5-MDMP.…”
Section: Discussionmentioning
confidence: 99%